One-way street and other writings - Benjamin, Walter 1892-1940 (Verso, 2021)
"Since his tragic death fleeing the Nazis in 1940, Walter Benjamin's reputation has only grown over the years, affirming his position as one of the most important intellectuals of the 20th century. "One-Way Street" is a cornerstone of the Benjamin legacy, exhibiting the richness and multidimensional nature of his thought. Included here are his famous essays on the history of Surrealism and photography; the personal and confessional writing on cities in "Hashish in Marseille" and "Naples"; and his powerful and fragmented recollections of fin de siècle Berlin; alongside his foundational essays on language, violence, psychology, aesthetics, and politics"--
Includes bibliographical references and index
Keywords: Benjamin, Walter / 1892-1940 / Translations into English; Essays